Biosorption of lead (II) ion from aqueous solution using dum palm kernel - Gutti, Babagana; Iyodo, Habu Mohammed; Isah, Umar Abdullahi (International Journal of Environment, 2015)
Biosorption of the lead ions from aqueous solutions using dum palm kernel was studied, the lead ion removal depends on the contact time, pH and adsorbent dosage. The optimum contact time, pH and adsorbent mass with in the experimental limit of this work were 100 minutes, 6-7, and 2.5g/L respectively. The maximum percentage of lead ions removed was 87%. The data fitted well with Temkin and Langmuir models, the regression correlation were obtained to be 0.9660 and 0.8667, respectively. The biosorbent may be economical if developed further for industrial wastewater and natural contaminated water treatment. DOI: http://dx.doi.org/10.3126/ije.v4i2.12625 International Journal of Environment Vol.4(2) 2015: 68-75